Systems and Frameworks for Computational Morphology Second International Workshop, SFCM 2011, Zurich, Switzerland, August 26, 2011. Proceedings - Mahlow, Cerstin; Piotrowski, Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the Second International Workshop on Systems and Frameworks for Computational Morphology, SFCM 2011, held in Zurich, Switzerland in August 2011. The eight revised full papers presented together with one invited paper were carefully reviewed and selected from 13 submissions. The papers address various topics in computational morphology and the relevance of morphology to computational linguistics more broadly.
Keywords: Computer science; Artificial intelligence; Translators (Computer programs).; Computational linguistics; Computer Science; Artificial Intelligence (incl. Robotics).; Language Translation and Linguistics; Computational Linguistics